Optimizing Sustainable Development: Increasing the Professionalism of Madrasah Teachers - Solehan Solehan (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
This article discusses strategies for optimizing sustainable development to increase the professionalism of madrasa teachers. Sustainable development is a systematic and ongoing effort aimed at improving teacher competence, performance and motivation in carrying out their duties. In the madrasa context, increasing teacher professionalism is not only important to improve the quality of education, but also to support the achievement of the goals of holistic Islamic education. Through descriptive qualitative research methods, this article identifies several key factors that influence madrasa teacher professionalism, including training and development, supervision, and school culture. The research results show that training programs that are sustainable and relevant to teachers' needs, support from madrasah leaders, and a conducive work environment, play a crucial role in increasing teacher professionalism. This article suggests implementing a sustainable development program integrated with regular evaluation to ensure its effectiveness. In this way, it is hoped that the professionalism of madrasa teachers can be increased significantly, which in turn will have a positive impact on the quality of education and the formation of students' character.